Catechins-Modified Selenium-Doped Hydroxyapatite Nanomaterials for Improved Osteosarcoma Therapy Through Generation of Reactive Oxygen Species - Khan, Suliman; Ullah, Muhammad Wajid; Siddique, Rabeea; Liu, Yang; Ullah, Ismat; Xue, Mengzhou; Yang, Guang; Hou, Hongwei (Frontiers in Oncology, 2019)
Osteosarcoma is the most common bone cancer with limited therapeutic options. It can be treated by selenium-doped hydroxyapatite owing to its known antitumor potential. However, a high concentration of Se is toxic toward normal and stem cells whereas its low concentration cannot effectively remove cancer cells. Therefore, the current study was aimed to improve the anticancer activity of Se-HAp nanoparticles through catechins (CC) modification owing to their high cancer therapeutic value. The sequentially developed catechins modified Se-HAp nanocomposites (CC/Se-HAp) were characterized for various physico-chemical properties and antitumor activity. Structural analysis showed the synthesis of small rod-like single phase HAp nanoparticles (60 ± 15 nm), which effectively interacted with Se and catechins and formed agglomerated structures. TEM analysis showed the internalization and degradation of CC/Se-HAp nanomaterials within MNNG/HOS cells through a non-specific endocytosis process. Cell toxicity analysis showed that catechins modification improved the antitumor activity of Se-HAp nanocomposites by inducing apoptosis of human osteosarcoma MNNG/HOS cell lines, through generation of reactive oxygen species (ROS) which in turn activated the caspase-3 pathway, without significantly affecting the growth of human normal bone marrow stem cells (hBMSCs). qPCR and western blot analyses revealed that casp3, p53, and bax genes were significantly upregulated while cox-2 and PTK-2 were slightly downregulated as compared to control in CC/Se-HAp-treated MNNG/HOS cell lines. The current study of combining natural biomaterial (i.e., catechins) with Se and HAp, can prove to be an effective therapeutic approach for bone cancer therapy.